Developing Religious Moderation in Indonesian Islamic Schools Through the Implementation of the Values of Islām Wasaṭiyyah - Muqowim, Muqowim; Sibawaihi, Sibawaihi; Alsulami, Naif Daifullah (Yogyakarta: Jurusan Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2022)
Purpose – This study aims at identifying the importance of religious moderation through understanding and practicing the values of Islām wasaṭiyyah in the learning process in Indonesian madrasah. Design/methods/approach – Using a historical approach, this qualitative study investigates the practices of the values of Islām wasaṭiyyah by medieval Muslim figures and explores indicators of success in learning based on those values in madrasah. Data were collected through document analysis. Document data sources were obtained from various literature, including books, ulama fatwas, scientific journals, seminar papers, and other publications. Data analysis techniques use content analysis based on themes found Findings – The authors found that of the seven values selected—tolerance, egalitarian, dynamic and innovative, reform, taking the path middle, balance, and prioritizing the priority—the figures practiced them simultaneously. The indicators of success in learning are students, teachers, and parents have an awareness of the importance of the values of wasaṭiyyah; students become the center of pedagogy reflecting those values; students and teachers act independently in implementing those values; students and teachers are involved in collaboration in developing those values; and there is transformation to the better one due to the inculcation of those values. Research implications/limitations – Because the study applies a historical approach, it uses only documents as its data source. Future studies can use interviews and observations so that the results are more trustworthy. Originality/value – The findings of the study provide an overview of the extent to which the values of Islām wasaṭiyyah have been practiced in Islamic schools in Indonesia.